Perbaikan Usaha Peternakan Sapi dengan Penguatan Kelembagaan dan Peningkatan Pengetahuan Reproduksi di Kelompok Parna Saiyo, Kecamatan Pauh Padang - Ediset Ediset; Amrizal Anas (Warta Pengabdian Andalas, 2019)
The service activities carried out aim to 1) Strengthen the group institutionally and 2) Increase breeders' knowledge about cattle reproduction. Institutional strengthening of the group is very important for the progress of the group because groups that have legality, dynamic and solid will easily access support from the government, while the technical aspects of breeder's reproduction must have knowledge and skills in order to increase production from the farm business itself. The beneficiaries of this community service activity was cattle farmers in the Parna Saiyo Group in Pauh District, Padang City. The method of activity applied was outreach and field meetings. The counseling was carried out to strengthen the group institutionally and the field meeting method was used to provide material on cattle reproduction. The results of the activity showed that members understood the importance of an institutionally strong group to get support from the government and the private sector, and an increase in group member knowledge on aspects of cattle reproduction.